Media roles, and ethics: perceptions of Brazilian, American and French journalist - Herckovitz, Heloiza (Brazilian journalism research, 2005)
This paper analyzes self-perceptions of media roles and ethics of a sample of Brazilian journalists and compares them with American and French journalists. French and American styles of journalism have had major inﬂ uences on Brazilian newspapers at different points in time. The study included a self-administered survey with 402 journalists working for 13 leading news organizations and personal interviews with renowned journalists of Sao Paulo- Brazil’s main media hub.  The typical Brazilian journalist in this study was a young white middle-class male, politically left leaning oriented, more likely to be married and Catholic. Respondents held a pluralistic view regarding media roles and expressed higher tolerance of controversial journalistic practices compared to that of their counterparts. Findings are in line with the social-political environment in which journalists operate. They do not enjoy special rights of access to government information, tend to distrust public institutions and have still been adapting to press freedom since the country’s redemocratization.